The Effect of The 8-Week Core Muscle Training in Swimming Time, Swimming Force and Core Muscle Activity Among Swimmers: A Randomized Controlled Trial. - Kwok, Wan-Yu; So, Billy Chun-Lung; Psycharakis, Stelios G.; Ng, Shamay Sheung-Mei (Journal of Sports Science & Medicine, 2025)
This intervention was conducted to evaluate the effects of 8 weeks of core training on swimming performance, force performance and core muscle activation. An 8-week core training was implemented, 32 swimmers were randomly allocated to experimental group (EG) (age: 14.38-14.88) and control group (CG) (age: 15.33-17.40). The CG maintained regular in-water training, while EG performed two additional core training a week. Swimming time, stroke rate (SR), stroke length (SL) and bilateral core muscle activity were obtained through 50 m front-crawl (FC) time trials and surface electromyography (sEMG). Moreover, the tethered swimming force was measured using the Tethered Swimming Test (TST) as a kinetic parameter. All tests were performed twice (pre- and post-intervention) to examine differences in measured parameters. No between-group differences were found. Male swimmers in EG showed within group decrease in swimming time (- 0.59 s; p < 0.05; ES = 0.827), while female swimmers in both groups showed changes in swimming velocity (EG: + 0.03 m/s; CG: + 0.02 m/s; p < 0.05). EG in male and female swimmers showed more improvement in TST than CG. For the co-contraction index (CCI) of the core muscle, no differences were demonstrated in female and male groups. This study did not indicate significant effects of core training on swimmers, additional research exploring core training is recommended to confirm these findings.